# RFC Errata

Found 2 records.

## Status: Verified (1)

### RFC 6090, "Fundamental Elliptic Curve Cryptography Algorithms", February 2011

Source of RFC: IETF - NON WORKING GROUPArea Assignment: sec

Errata ID: 3920

**Status: Verified
Type: Technical
Publication Format(s) : TEXT**

Reported By: Watson Ladd

Date Reported: 2014-03-15

Verifier Name: Kathleen Moriarty

Date Verified: 2014-07-01

Section Appendix F says:

Then, the product P3=(X3,Y3,Z3) = P1 * P2 is given by: if P1 is the point at infinity, P3 = P2 else if P2 is the point at infinity, P3 = P1 else if u is not equal to 0 but v is equal to 0, P3 = (0,1,0) else if both u and v are not equal to 0, X3 = v * (Z2 * (Z1 * u^2 - 2 * X1 * v^2) - v^3) Y3 = Z2 * (3 * X1 * u * v^2 - Y1 * v^3 - Z1 * u^3) + u * v^3 Z3 = v^3 * Z1 * Z2 else // P2 equals P1, P3 = P1 * P1 w = 3 * X1^2 + a * Z1^2 X3 = 2 * Y1 * Z1 * (w^2 - 8 * X1 * Y1^2 * Z1) Y3 = 4 * Y1^2 * Z1 * (3 * w * X1 - 2 * Y1^2 * Z1) - w^3 Z3 = 8 * (Y1 * Z1)^3

It should say:

Then, the product P3=(X3,Y3,Z3) = P1 * P2 is given by: if P1 is the point at infinity, P3 = P2 else if P2 is the point at infinity, P3 = P1 else if P1=-P2 as projective points P3 = (0,1,0) else if P1 does not equal P2 X3 = v * (Z2 * (Z1 * u^2 - 2 * X1 * v^2) - v^3) Y3 = Z2 * (3 * X1 * u * v^2 - Y1 * v^3 - Z1 * u^3) + u * v^3 Z3 = v^3 * Z1 * Z2 else // P2 equals P1, P3 = P1 * P1 w = 3 * X1^2 + a * Z1^2 X3 = 2 * Y1 * Z1 * (w^2 - 8 * X1 * Y1^2 * Z1) Y3 = 4 * Y1^2 * Z1 * (3 * w * X1 - 2 * Y1^2 * Z1) - w^3 Z3 = 8 * (Y1 * Z1)^3

Notes:

The original algorithm was wrong and produces incorrect answers. There are several fixes that could take place.

## Status: Reported (1)

### RFC 6090, "Fundamental Elliptic Curve Cryptography Algorithms", February 2011

Source of RFC: IETF - NON WORKING GROUPArea Assignment: sec

Errata ID: 6329

**Status: Reported
Type: Editorial
Publication Format(s) : TEXT**

Reported By: Yannik Klubertanz

Date Reported: 2020-11-06

Section F.1. says:

if P is (@,@), R = Q else if Q is (@,@), R = P else if P is not equal to Q and x1 is equal to x2, R = (@,@) else if P is not equal to Q and x1 is not equal to x2, x3 = ((y2-y1)/(x2-x1))^2 - x1 - x2 mod p and y3 = (x1-x3)*(y2-y1)/(x2-x1) - y1 mod p else if P is equal to Q and y1 is equal to 0, R = (@,@) else // P is equal to Q and y1 is not equal to 0 x3 = ((3*x1^2 + a)/(2*y1))^2 - 2*x1 mod p and y3 = (x1-x3)*(3*x1^2 + a)/(2*y1) - y mod p.

It should say:

if P is (@,@), R = Q else if Q is (@,@), R = P else if P is not equal to Q and x1 is equal to x2, R = (@,@) else if P is not equal to Q and x1 is not equal to x2, x3 = ((y2-y1)/(x2-x1))^2 - x1 - x2 mod p and y3 = (x1-x3)*(y2-y1)/(x2-x1) - y1 mod p else if P is equal to Q and y1 is equal to 0, R = (@,@) else // P is equal to Q and y1 is not equal to 0 x3 = ((3*x1^2 + a)/(2*y1))^2 - 2*x1 mod p and y3 = (x1-x3)*(3*x1^2 + a)/(2*y1) - y1 mod p.

Notes:

In the last case in the pseudocode, there's a typo. It should be "y1" mod p instead of "y mod p".